2012
DOI: 10.1002/cmmi.1473
|View full text |Cite
|
Sign up to set email alerts
|

Uniform mesoporous silica coated iron oxide nanoparticles as a highly efficient, nontoxic MRI T2 contrast agent with tunable proton relaxivities

Abstract: Core–shell magnetic nanostructures (MNS) such as Fe3O4–SiOx, are being explored for their potential applications in biomedicine, such as a T2 (dark) contrast enhancement agent in magnetic resonance imaging (MRI). Herein, we present the effect of silica shell thickness on its r2 relaxivity in MRI as it relates to other physical parameters. In this effort initially, monodispersed Fe3O4 MNS (nominally 9 nm size) were synthesized in organic phase via a simple chemical decomposition method. To study effect of shell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 50 publications
4
80
0
Order By: Relevance
“…This result makes their use as negative CA for MRI promising. The same negligible effect T 1 although in a smaller scale was reported for a silica coated SPIONs [14].…”
Section: Nuclear Magnetic Relaxivitiessupporting
confidence: 78%
See 3 more Smart Citations
“…This result makes their use as negative CA for MRI promising. The same negligible effect T 1 although in a smaller scale was reported for a silica coated SPIONs [14].…”
Section: Nuclear Magnetic Relaxivitiessupporting
confidence: 78%
“…It is a fact that several SPIONs present higher r 2 values [14] but the NPs here studied have outstanding ratios r 2 /r 1 . Since all the synthesized NPs have the same superparamagnetic core, the observed differences in the ratio r 2 /r 1 mus be assigned to the coating.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Metal oxides such as TiO 2 and SiO 2 including calcium phosphate coating over nanoparticles are well studied by several researchers. [47][48][49] Yang et al synthesized mesoporous and nonmesoporous silica-coated iron oxide nanoparticles for luminescent and drug delivery applications. 47 Ye et al reported the synthesis of mesoporous silica-coated iron oxide nanoparticles for use as nontoxic MRI contrast agent.…”
mentioning
confidence: 99%